1997
DOI: 10.1598/rrq.32.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Television's Impact on Children's Reading Comprehension and Decoding Skills: A 3‐Year Panel Study

Abstract: S Using a sample of 1,050 Dutch elementary school children who were in Grades 2 and 4 at the outset of the research, this study explored (a) the longitudinal effects of television viewing on children's reading comprehension, (b) the causal mechanisms that underlie television's longitudinal effects on reading comprehension, and (c) the longitudinal effects of television viewing on children's decoding skills. The children were surveyed three times, at 1‐year intervals. Structural equations analyses suggested tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0
10

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 26 publications
4
58
0
10
Order By: Relevance
“…[6][7][8][9]11,13,14,16 In addition, they support the inference that attention difficulties, frequent failure to complete homework, and negative attitudes toward school may each play an important mediating role in the association between extensive television viewing during adolescence and ultimate educational failure. These findings add to a growing body of evidence indicating that frequent entertainment and general audience television viewing during adolescence may be associated with risk for the development of a wide range of cognitive and behavioral deficits that are associated with risk for poor longterm educational achievement.…”
Section: Commentmentioning
confidence: 77%
See 3 more Smart Citations
“…[6][7][8][9]11,13,14,16 In addition, they support the inference that attention difficulties, frequent failure to complete homework, and negative attitudes toward school may each play an important mediating role in the association between extensive television viewing during adolescence and ultimate educational failure. These findings add to a growing body of evidence indicating that frequent entertainment and general audience television viewing during adolescence may be associated with risk for the development of a wide range of cognitive and behavioral deficits that are associated with risk for poor longterm educational achievement.…”
Section: Commentmentioning
confidence: 77%
“…[1][2][3][4]15 Frequent viewing of entertainment and general audience television programming during childhood and adolescence has been hypothesized to contribute to persistent reductions in educational and intellectual functioning 14 because it displaces reading and homework, requires relatively little intellectual effort, and promotes attention problems and disinterest in school. 2,6,7,11,16,17 Research findings supporting this hypothesis have indicated that overall television viewing time during childhood and adolescence may be associated with elevated risk for the development of attention problems, educational difficulties, poor reading comprehen-sion, and other cognitive deficits. [6][7][8][9]11,13,14 Entertainment and general audience television viewing may be differentially associated with decreases in reading and educational activities, and informative programs designed for children may be associated with improvements in letter and word recognition.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…When it comes to the effects of television consumption results seem equivocal. Scholars testing displacement theory show that especially lowbrow (entertainment) television consumption absorbs time that otherwise might be spent on educational activities, like doing homework and reading (Hancox et al, 2005;Koolstra, Van der Voort, & Van der Kamp, 1997). Other studies, find that watching educational television programs enhances children's school readiness (Wright et al, 2001).…”
Section: Socialization By Parental Media Guidancementioning
confidence: 99%